The Network of Islamic Radicalism: Proposing a Mapping Model - Mutaqin, Zezen Zaenal (Islamic Studies Review, 2022)
This paper deals with both a theoretical and practical aspect of mapping of the global radical Muslim groups. It will propose a typology of global Muslim radical groups that will be used to formulate a unified pattern and frame to be integrated into a practical and institutional strategy. While the primary purpose is to create a typology and mapping of actors and its activism, this paper also attempts to answer a more profound question related to the cause of divergence, split, and conflict within the global radical networks. The article will show that the global Islamic radical network is deeply rooted in a local context. Almost all global radical organizations thrived in a failed state where state controls and authorities were absent, and its fabric of society was broken by ongoing ethnic and sectarian conflicts, socio-economic crisis, as well as foreign interventions. Borrowing the social movement theory, this paper elaborates Islamic radicalism movement in a broader picture of Islamic activism where its scope covers both peaceful and violence activism. By taking cases from Southeast Asia, the Middle East, and Africa, this paper not only proposes the analysis on the dynamics of Islamic radicalism in a broader landscape but also highlights the matter in a comparative perspective.